2016
DOI: 10.5194/esd-7-597-2016
|View full text |Cite
|
Sign up to set email alerts
|

Comment on "Scaling regimes and linear/nonlinear responses of last millennium climate to volcanic and solar forcing" by S. Lovejoy and C. Varotsos (2016)

Abstract: Abstract. (L&V) analyse the temperature response to solar, volcanic, and solar plus volcanic forcing in the Zebiak-Cane (ZC) model, and to solar and solar plus volcanic forcing in the Goddard Institute for Space Studies (GISS) E2-R model. By using a simple wavelet filtering technique they conclude that the responses in the ZC model combine subadditively on timescales from 50 to 1000 years. Nonlinear response on shorter timescales is claimed by analysis of intermittencies in the forcing and the temperature s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our analysis of the spectral gain was limited to global average values and those timescales where linearity can be reasonably assumed [39,40,100]. Nonlinearities are inherent to the climate system, for example, due to the temperature-albedo feedback.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our analysis of the spectral gain was limited to global average values and those timescales where linearity can be reasonably assumed [39,40,100]. Nonlinearities are inherent to the climate system, for example, due to the temperature-albedo feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Mean spectra were calculated by interpolation to the lowest resolution, binning into equally spaced log-frequency intervals, and taking the average with equal weights [23]. This requires the statistical independence of the averaged values [40]. The spectral exponent β is calculated by linear regression to the logarithm of (1) on periods between τ 1 = 10 and τ 2 = 200 years.…”
Section: A Spectral Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Scaling of paleo-climate data has received a lot of attention (e.g., Bunde et al, 2014;Huybers & Curry, 2006;Laepple & Huybers, 2013;Lovejoy & Schertzer, 2013;Lovejoy & Varotsos, 2016;Nilsen et al, 2016;Rypdal & Rypdal, 2016a;Schmitt et al, 1995;Zhu et al, 2019) and has been used in evaluating how well climate models reproduce observed long-term climate variability (Blender et al, 2006;Østvand et al, 2014). While global mean temperature variability on interannual to millennial time scales seems to be consistent between climate models and climate reconstructions, the strong discrepancy of slow climate variability at regional scales calls for continued research on the temporal and spatial structures of climate variability and also on improving the interpretation and quality of paleo-climate records.…”
Section: 1029/2019rg000657mentioning
confidence: 99%